Numerical investigation on sound transmission behaviour of multilayered panels with periodic arrays of spring-mass resonators - Jovanoska, Milica; Samardzioska, Todorka (European Acoustics Association, 2022)
Recent developments in engineering and sustainability initiatives have resulted in building trend of lightweight partitions, utilizing new materials and technologies. At the same time, noise pollution is becoming a growing problem across the globe, as a result of present-day life dynamics. The impact of the increased noise levels on human health and wellbeing is perceived. All this implies the need for sound insulation enhancement of the lightweight partitions. Theoretical and numerical investigation of multi-layered panels under acoustic excitation are conducted using different methods. The sound transmission loss (STL) of unbounded multi-layered panels is calculated using the theory of three- dimensional elasticity and well-known transfer matrix method (TMM). Additionally, the finite element method (FEM) is also used for sound transmission loss calculation and for obtaining the dispersion diagrams. Based on the dispersion curves, detection of the band gaps is made possible. In order to improve the sound transmission loss in a specific frequency region, periodic resonant units (spring-mass resonators) are tuned and introduced to the considered panels. It can be shown that the resonance mode of the spring-mass resonators couples with the plate vibration in the way of breaking the mass law and overcoming some phenomena like coincidence effect and mass-air-mass resonance. These units can be attached or embedded in the host panel. Such periodic structures recently have been recognized as acoustic metamaterials. Acoustic resonant metamaterials are artificial periodic structures with unique acoustic wave manipulation properties, owing to the dynamic influence of their local resonant units. The drawback of this concept is that this ”unordinary” power for wave manipulation works only in specific narrow frequency band associated with the resonant frequency of the resonant units. Nevertheless, this phenomenon has potential to be useful ”tool” for correcting/complementing lightweight partition systems.